Citizen Marx republicanism and the formation of Karl Marx's social and political thought - Leipold, Bruno (Princeton University Press, 2024)
"A compelling and comprehensive analysis of Marx's social and political thought, primarily as it relates to his underappreciated republicanism"--
Keywords: Marx, Karl -- 1818-1883; Geschichte; Politisches Denken; Marx, Karl / 1818-1883; Republicanism; Communism; Philosophy, Marxist